Bee pollination in agricultural ecosystems - James, Rosalind R.; Pitts-Singer, Theresa L. (Oxford : Oxford University Press, 2008)
Managed and wild bees are critical for successful pollination of numerous fruit, vegetable, oilseed and legume seed crops and both are considered here. So is treatment of how bees also impact the agro-ecosystem in ways beyond simple pollination such as by transporting pollen from genetically modified plants.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bees -- Control -- Environmental aspects; Pollination by insects; Agricultural ecology; Bees -- Ecology